(untitled) (Bangladesh Journal of Botany, 2022)
Flowers of Cassia fistula L. were collected from Lahore, Pakistan and extracted in methanol followed by separation of n-hexane soluble compounds in a separating funnel. The separated n-hexane phase was analyzed by GC-MS for identification of various possible phytochemicals. Among the 31 identified compounds, the predominant compound in this fraction was butanoic acid, methyl ester with 17.81% peak area followed by 3-eicosene, (E)- (6.83%), 2-ethylformanilide (6.59%), naphthalene (6.10%), trifluoroacetoxy hexadecane (5.88%), 5-octadecene, (E)- (5.58%), phenylethanolamine (5.09%), 1-hexene- 3,5-dione (4.68%) tetratetracontane (3.42%), which were ranked as moderately abundant compounds. Eleven compounds including benzenebutanamine (3.80%), heptadecyl trifluoroacetate (3.65%), heptadecane (3.08%), octadecyl trifluoroacetate (2.30%), 2-pyrrolidinone, 1-methyl- (1.78%), 1-undecanol (1.64%), ethylene glycol, O,O-di(pivaloyl)- (1.48%), benzyl alcohol (1.38%), hexadecanoic acid, 15-methyl-, methyl ester (1.32%), 1-docosene (1.27%) and heneicosane (1.25%), with their peak areas between 1 and 4% were categorized as less abundant compounds. The remaining 9 compounds with peak areas less than 1% were categorized as least abundant or minor compounds. Bangladesh J. Bot. 51(2): 393-399, 2022 (June)